Low-fouling biomimetic membranes fabricated by direct replication of self-cleaning natural leaf. Issue 23 (15th October 2021) - Madaeni, S. S.; Falsafi, M.; Ghaemi, N.; Daraei, P.
ABSTRACT: The membrane fouling has always been a big issue for developing membrane applications. Surface morphology and roughness affect remarkably on the membrane tendency to fouling. In this study, a biomimetic technique, as a simple, cost-effective and time-saving method was employed to replicate Tropaeolum majus (nasturtium) leaf surface on the surface of a commercial thin-film composite (TFC) reverse osmosis (RO) membrane using polyethersulfone (PES) moulds. Morphology of surface and hydrophilicity of membranes were investigated by scanning electron microscope (SEM), atomic force microscope (AFM) and water contact angle measurements. AFM and SEM photos of membrane surface declared that replication of nasturtium leaf improved the surface characteristics of membranes. The average roughness of membranes heated at 130°C and 150°C was 81.1 and 152.4 nm, respectively. The similar measurement was lower for the virgin membrane. Also, the roughened membranes showed higher hydrophilicity than the virgin membrane. In addition, the performance of the membrane was assessed by evaluating pure water flux (PWF) and flux recovery (FR) after the filtration of whey solution as a severe foulant for membranes. The findings exhibited that the replicated membranes had higher PWF and FR values, indicating the lower fouling tendency of modified membranes. GRAPHICAL ABSTRACT: UF0001